1995
DOI: 10.1111/j.1476-5381.1995.tb16366.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of a novel form of hippocampal long‐term depression by muscimol: involvement of GABAA but not glutamate receptors

Abstract: 1 Unlike long-term potentiation, long-term depression (LTD) 4 Adenosine decreased the spike size in a concentration-dependent manner, but failed to induce LTD. 5 Alphaxalone and 5a-pregnan-3a-ol-20-one at concentrations that did not have any effect themselves on the population spike (0.5 and 1 gM), potentiated the inhibitory effect of muscimol on the population spike size, including concentrations which were not effective by themselves. Both steroids were able to potentiate the ability of muscimol to induce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Alternatively, this effect could underlie a form of long‐term synaptic plasticity, i.e. long‐term depression, as shown previously in the hippocampus (Akhondzadeh & Stone 1995).…”
Section: Discussionmentioning
confidence: 60%
“…Alternatively, this effect could underlie a form of long‐term synaptic plasticity, i.e. long‐term depression, as shown previously in the hippocampus (Akhondzadeh & Stone 1995).…”
Section: Discussionmentioning
confidence: 60%
“…That 2 h treatments were able to affect metaplasticity is not surprising because of previous reports showing rapid triggering and reversal of metaplastic changes (Abraham and Bear, 1996;Shakesby et al, 2002). Application of muscimol or zolpidem increases GABA A receptor-mediated currents and reduces spiking and excitatory postsynaptic potentials (Rovira et al, 1984;Akhondzadeh and Stone, 1995;Steele and Mauk, 1999;Hajos et al, 2000;Liang et al, 2004). Two other treatments of slices from TNRϪ/Ϫ mice, namely with the GABA B receptor antagonist CGP54626A and the HNK-1 peptidomimetic, produced a similar normalization of LTP as GABA A receptor agonists.…”
Section: Discussionmentioning
confidence: 87%
“…Several neurotransmitters, such as glutamate, dopamine, adenosine, and serotonin contribute to the induction of endocannabinoid-dependent LTD in the striatum (Lovinger 2010;Tozzi et al 2011;Lerner and Kreitzer 2012;Burattini et al 2014). Although GABA is the most important inhibitory neurotransmitter in the brain, few studies have examined its ability to induce synaptic plasticity at glutamatergic synapses (Akhondzadeh and Stone 1995). We recently found that the GABA A receptor agonist muscimol induced a long-lasting inhibition of glutamatergic synaptic transmission in the NAc in adolescent but not adult mice (Mishra and Chergui 2013).…”
mentioning
confidence: 99%